Building Student Engagement with Google Spaces - Peg Hohensee (Academic Chairpersons Conference Proceedings, 2023)
Google Spaces is an easy to setup group chat that could help with community building and communication. The presenter will demonstrate creating a Google Space. The presenter will also discuss the results of having used a Google Space with a class and brainstorm with participants uses for future classes.
Keywords: engagement; community building; communication; technology; Google